Innovative biopolymers composite based thin film for wound healing applications - Majid Ali; Shakir Ullah; Shaker Ullah; Muhammad Shakeel; Tayyaba Afsar; Fohad Mabood Husain; Houda Amor; Suhail Razak (Scientific Reports)
Abstract Efficient wound and burn healing is crucial for minimising complications, preventing infections, and enhancing overall well-being, necessitating the development of innovative strategies. This study aimed to formulate a novel thin film combining chitosan, carboxymethyl cellulose, tannic acid, and beeswax for improved wound healing applications. Several formulations, incorporating chitosan, carboxymethyl cellulose, tannic acid, and beeswax in various percentages, were utilized to deposit thin films via the solvent evaporation technique, Mechanical properties, morphology, antioxidant activity, antibacterial efficacy, and wound healing potential were evaluated. The optimized thin film (M4), composed of 2% chitosan, 2% carboxymethyl cellulose, and 1% tannic acid, along with 0.2% glycerol and 0.2% tween80, exhibited a thickness of 39.0 ± 1.14 μm and a tensile strength of 0.275 ± 0.003 MPa. It demonstrated a swelling degree of 283.0 ± 2.0% and a drug release capacity of 89.4% within 24 h. The film also showed a low contact angle of 40.5° and a water vapour transmission rate of 1912.25 ± 13.10 g m−2 0.24 h−1. FT-IR spectroscopy indicated that chitosan and carboxymethyl cellulose were cross-linked through amide linkages, with tannic acid occupying the interstitial spaces and hydrogen bonding stabilizing the structure. Microscopy of M4 revealed a uniform morphology. The film exhibited strong antioxidant activity of (95.17 ± 0.02%) and antibacterial efficiency (80.8%) against S. aureus. In a rabbit model, the film significantly enhanced burn and excision wound recovery, with 90.0 ± 3.3% healing for burns and 88.85 ± 1.7% for infected wounds by day 7. Complete skin regeneration was observed within 10–12 days. The M4 thin film demonstrated exceptional mechanical properties and bioactivity, offering protection against pathogens and promoting efficient wound healing. These findings suggest its potential for further investigation in treating various infections and its role in developing novel therapeutic interventions.